Hermeneutik Sebagai Tawaran Metodologis dalam Menafsirkan Al-Quran yang Diperdebatkan - Mabrur, Hajjin; Abas, Saehu (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The presence of 'Ulum al-Qur'an as formulated by the scholars cannot be separated from efforts to anticipate the potential diversity of meanings contained in the Qur'an. Thus, the history of the birth of the sciences of the Koran ('Ulum al-Qur'an) cannot be separated from the history of the diversity of meanings of the Koran. The concepts summarized in the 'Ulum al-Qur'an such as nasikh-mansukh, makki-madani, 'am-khash, muthlaq-muqayyad, asbab al-nuzul, dzahir-bathin and the like are a set of concepts that show and have implications for the presence of various interpretations. As far as methodological discourse is concerned, there is currently a new awareness of the importance of involving the social sciences—psychology, sociology, anthropology and history—and the humanities—philosophy, hermeneutics and linguistics—in understanding the holy text of the Koran. From this, a new term developed in the discourse and activity of interpreting the text of the holy book of the Koran, namely hermeneutics—in particular, hermeneutics of the Koran. Al-Qur'an hermeneutics is understood as the science and art of interpretation of the Koran, which includes theory, methodology and techniques of interpretation of the Koran. There are two major groups of scholars in responding to the hermeneutic offer in exploring the meaning of the Koran, namely the first group refuses for reasons including because "we" already have ulumul Quran which has been tested and proven successful in uncovering the meaning and intent of the verses of al-Qur'an. -Qur'an, and the second group accepts with reasons and limitations. Among the reasons is that we must be open to positive new things, of course, by remaining critical. When there is something new that is better than the old one, as a person with a healthy mind, of course, he will take the new thing. Therefore, when interpreters are going to adopt hermeneutics in interpreting the Qur'an, for example, they must know their knowledge first, so as not to cause things that could harm themselves or others.